Restoration of Foveal Bulge after Resolution of Diabetic Macular Edema with Coexisting Serous Retinal Detachment - Yijun Hu; Qiaowei Wu; Baoyi Liu; Manqing Huang; Qingsheng Peng; Pingting Zhong; Xiaomin Zeng; Yu Xiao; Cong Li; Ying Fang; Tao Li; Honghua Yu; et al. (Journal of Diabetes Research)
Purpose. To evaluate the impact of restoration of foveal bulge (FB) in optical coherence tomography (OCT) images on visual acuity after resolution of diabetic macular edema with coexisting serous retinal detachment (SRD-DME). Methods. A total of 52 eyes with resolved SRD-DME and an intact ellipsoid zone at the central fovea were included. All eyes underwent best-corrected visual acuity (BCVA) examination and OCT scanning at baseline and follow-up visits (1, 3, and 6 months). The eyes were divided into two groups according to the presence of FB at 6 months. BCVA, central foveal thickness (CFT), height of SRD (SRDH), outer nuclear layer (ONL) thickness, photoreceptor inner segment (PIS), and outer segment (POS) length were compared between the two groups. Results. A FB was found in 25 of 52 (48%) eyes at 6 months. The FB (+) group had lower SRDH at baseline, and better BCVA, longer POS length at 6 months (all P<0.05). There was no significant difference in the CFT, ONL thickness, and PIS length at 6 months between the two groups (all P>0.05). More eyes in the FB (+) group had complete SRD resolution at 1 month (P=0.009) and 3 months (P=0.012). Eyes with complete SRD resolution at 1 month (P=0.009) or 3 months (P=0.012) were more likely to have a FB at 6 months. Conclusions. The Presence of the FB is associated with better BCVA after resolution of SRD-DME. Eyes with lower baseline SRDH or faster SRD resolution are more likely to have a FB at 6 months.